CHARACTERIZATION OF ANDIGENA ACCESSIONS FOR BIOTIC STRESS RESISTANCE USING LINKED MOLECULAR MARKERS - Sood, Salej (Potato Journal, 2023)
ABSTRACT: In the current study, 72 andigena accessions were screened for resistance to late blight, viruses (PVY and PVX), and potato cyst nematodes (PCNs) using gene-based linked markers. R1 gene was only present in one accession, JEX-A/668. Whereas two accessions, JEX-A/459 and JEX-A/616, showed the presence of the R2 gene. The R3a gene was not present in any of the accessions. The R3b gene was also amplified in the JEX-A/42, JEX-A/107, and JEX-A/459 accessions. In PVY resistance screening, the YES3-3A marker was found in 50 accessions. In comparison, 40 accessions tested positive for the STM0003 marker, which indicates the presence of the Rysto gene, whereas 14 accessions tested positive for the RYSC3 marker. In 9 and 20 accessions, respectively, the markers 1Rx1 and 106Rx2, which were connected to the extreme resistance genes Rx1 and Rx2 for PVX resistance, were discovered. Both 1Rx1 and 106Rx2 markers were discovered in six accessions (JEX-A/232, JEX-A/267, JEX-A/638, JEX-A/683, JEX-A/1061, and JEX-A/1092). Globodera spp. resistance screening revealed that 17 out of 72 accessions tested positive for the marker TG689. None of the accessions was positive for the SPUD1636 marker. Furthermore, the expected-size bands for the GPA2-1 and GPA2-2 markers, 1120 and 452 bp, respectively, were found in 15 separate accessions. Both markers show the presence of the Gpa2 locus, which almost completely confers resistance to one or more pathotypes of G. pallida.